Association of red cell distribution width with clinical outcomes in myelodysplastic syndrome. (April 2018) - Baba, Yuta; Saito, Bungo; Shimada, Shotaro; Sasaki, Yohei; Murai, So; Abe, Maasa; Fujiwara, Shun; Arai, Nana; Kawaguchi, Yukiko; Kabasawa, Nobuyuki; Tsukamoto, Hiroyuki; Uto, Yui; et al.
Highlights: Red cell distribution width (RDW) in MDS might reflect dyserythropoiesis. The hemoglobin concentration was inversely correlated with RDW. The percentage of ringed sideroblasts in bone marrow was correlated with RDW. Increased RDW might have potential to be a prognostic factor in low-risk MDS. Abstract: Studies showed red cell distribution width (RDW) can improve the detection of morphological changes in red blood cells and the understanding of their contribution to dyserythropoiesis in myelodysplastic syndrome (MDS). The purpose of the study was to evaluate dyserythropoiesis in MDS by RDW analysis and to explore the utility of RDW in clinical practice. We retrospectively analyzed laboratory and clinical data of 101 patients (59 patients was refractory anemia (RA) according to the French-American-British (FAB) classification). In patients with RA, RDW was showed weak inverse correlation with both hemoglobin concentration (Hb) ( rs = −0.37, P = 0.0035) and mean corpuscular hemoglobin concentration (MCHC) ( rs = −0.36, P = 0.0047). On the other hand, RDW was showed weak correlation with the number of ringed sideroblasts in bone marrow ( rs = 0.31, P = 0.023). The increased RDW (≥15.0%) was associated with shorter overall survival (OS) ( P = 0.0086). In patients with refractory anemia with excess blasts (RAEB) and RAEB in transformation (RAEB-t), effect of RDW on OS was less evident. These results suggested that increased RDW might reflect dyserythropoiesis, associated with deregulated hemoglobin synthesis and iron metabolism in MDS. Furthermore, increased RDW may have potential to be a prognostic significance in RA.